Interactive Effects of Agitation and Cognitive Impairment on Odor Identification in Patients With Late-Life Depression - Zhang, Si; Chen, Ben; Zhong, Xiaomei; Zhang, Min; Wang, Qiang; Wu, Zhangying; Hou, Le; Zhou, Huarong; Chen, Xinru; Liu, Meiling; Yang, Mingfeng; Lin, Gaohong; et al. (Frontiers in Psychiatry, 2022)
Background: Late-life depression (LLD) patients are at high risk of developing dementia, and odor identification (OI) deficits is an early predictor of cognitive decline in LLD. However, neuropsychiatric symptoms (NPS) are common in LLD and associated with OI deficits. When using OI deficits to predict cognitive decline in LLD, whether NPS may be affect the effect of prediction remains unclear. Objective: To comprehensively explore the potential effect of various NPS on the relationship between OI and cognition in patients with LLD. Methods: One hundred and sixty-seven LLD patients and 105 normal elderly (NE) were recruited. Subjects underwent assessments of odor identification (Sniffin’ Sticks), cognitive function (global cognition, memory, executive function, attention, language, visual space), and NPS (the neuropsychiatric inventory questionnaire). Correlation analysis and moderation analysis were used to analyze the relationships between OI, cognition and NPS in LLD patients. Results: In LLD patients, OI was positively correlated with cognition (global cognition, memory, executive function, attention, language) and negatively associate with NPS (agitation, apathy, aberrant motor behavior). In NE, OI was correlated with MMSE, and OI was not significant correlated with any NPI scores. Moderation analysis shown that there was an interactive effect of agitation and cognitive impairment (language deficit or attention deficit) on OI in LLD. Conclusion: The coexistence of agitation and cognitive impairment was associated with worse OI in LLD patients, and studies exploring the association between OI and cognitive function should include an assessment of agitation and adjust its mixed effects.